Altered thalamic connectivity in insomnia disorder during wakefulness and sleep. Issue 1 (13th October 2020) - Zou, Guangyuan; Li, Yuezhen; Liu, Jiayi; Zhou, Shuqin; Xu, Jing; Qin, Lang; Shao, Yan; Yao, Ping; Sun, Hongqiang; Zou, Qihong; Gao, Jia‐Hong
Abstract: Insomnia disorder is the most common sleep disorder and has drawn increasing attention. Many studies have shown that hyperarousal plays a key role in the pathophysiology of insomnia disorder. However, the specific brain mechanisms underlying insomnia disorder remain unclear. To elucidate the neuropathophysiology of insomnia disorder, we investigated the brain functional networks of patients with insomnia disorder and healthy controls across the sleep–wake cycle. EEG‐fMRI data from 33 patients with insomnia disorder and 31 well‐matched healthy controls during wakefulness and nonrapid eye movement sleep, including N1, N2 and N3 stages, were analyzed. A medial and anterior thalamic region was selected as the seed considering its role in sleep–wake regulation. The functional connectivity between the thalamic seed and voxels across the brain was calculated. ANOVA with factors "group" and "stage" was performed on thalamus‐based functional connectivity. Correlations between the misperception index and altered functional connectivity were explored. A group‐by‐stage interaction was observed at widespread cortical regions. Regarding the main effect of group, patients with insomnia disorder demonstrated decreased thalamic connectivity with the left amygdala, parahippocampal gyrus, putamen, pallidum and hippocampus across wakefulness and all three nonrapid eye movement sleep stages. The thalamic connectivity in the subcortical cluster and the right temporal cluster in N1 was significantly correlated with the misperception index. This study demonstrated the brain functional basis in insomnia disorder and illustrated its relationship with sleep misperception, shedding new light on the brain mechanisms of insomnia disorder and indicating potential therapeutic targets for its treatment. Abstract : Thalamus‐based connectivity in patients with insomnia disorder and healthy controls during wakefulness and sleep was analyzed. A group‐by‐stage interaction was observed at widespread cortical regions. Regarding the main effect of group, patients with insomnia disorder demonstrated decreased thalamic connectivity with the left amygdala, parahippocampal gyrus, putamen, pallidum, and hippocampus across wakefulness and all three nonrapid eye movement sleep stages.